2022
DOI: 10.1507/endocrj.ej21-0615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a new 75 g glucose- and high fat-containing cookie meal test on postprandial glucose and triglyceride excursions in morbidly obese patients

Abstract: A new meal tolerance test (MTT) using a 75 g glucose-and high fat-containing meal was applied to classify glucose intolerance in morbidly obese patients. According to the MTT data, the concordance rate of diagnosis was 82.5% compared to the 75 g oral glucose tolerance test (OGTT) in patients with normal glucose tolerance (NGT, n = 40). In the NGT patients, the insulinogenic index (r = 0.833), Matsuda index (r = 0.752), and disposition index (r = 0.845) calculated from the MTT data were each significantly (p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…In that investigation, the MTT was demonstrated to be useful for determining the precise staging of impaired glucose tolerance compared to the 75-g OGTT. We also observed that this MTT meal containing saturated fat can be used to evaluate postprandial hypertriglyceridemia in morbidly obese patients [10].…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…In that investigation, the MTT was demonstrated to be useful for determining the precise staging of impaired glucose tolerance compared to the 75-g OGTT. We also observed that this MTT meal containing saturated fat can be used to evaluate postprandial hypertriglyceridemia in morbidly obese patients [10].…”
mentioning
confidence: 72%
“…The 75-g OGTT and MTT protocols were as we described [10]. Briefly, on the 2nd day after their hospital admission, the patients underwent a 75-g OGTT.…”
Section: The 75-g Ogtt and Mttmentioning
confidence: 99%
See 2 more Smart Citations
“…The triglyceride-insulin-glucose-glucagon-like peptide-1 model was built to assess glucose, insulin, and incretin responses following a high-fat meal ( 49 ). The OFTT can help patients identify insulin sensitivity impairments, insulin resistance, beta-cell dysfunctions and secretion disorders of gut hormones, including glucose-dependent insulinotropic polypeptides and glucagon-like peptide-1 ( 21 , 50 ).…”
Section: Discussionmentioning
confidence: 99%